INSTAGRAM CONTENT MARKETING STRATEGIES FOR HOSPITALITY BRAND IDENTITY: A CONTENT ANALYSIS OF @VASAHOTEL - Firman Aero Naradika; Diana Amalia (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to analyze the content marketing strategy implemented by the Instagram account @vasahotel in strengthening Vasa Hotel Surabaya's brand identity. A qualitative approach with Krippendorff's content analysis was employed to examine 20 Instagram posts published between July 2025 and February 2026. The analysis was guided by Pulizzi's content marketing dimensions, namely content mission, content tilt, and platform suitability, and interpreted using Kapferer's Brand Identity Prism. The findings indicate that @vasahotel utilizes Instagram not merely as a promotional medium but as a strategic platform for brand identity construction. Through content mission, Vasa Hotel Surabaya communicates its positioning as a premium hospitality brand integrating business, cultural, culinary, and lifestyle values. Content tilt differentiates the brand by transforming promotional messages into artistic, experiential, and storytelling-driven content. Meanwhile, platform suitability is reflected in the effective use of carousel and reels formats that align with Instagram's characteristics and audience behavior. Overall, the study demonstrates that content marketing contributes to reinforcing Vasa Hotel Surabaya's identity as a modern, premium, and experience-oriented hospitality brand.